Geochemical Characteristics of Gas and Flowback Water in Lake Facies Shale: A Case Study From the Junggar Basin, China - Zhang, Lin; Liu, Dan; Gao, Yongjin; Zhang, Min (Frontiers in Earth Science, 2021)
The chemical and isotopic compositions of the natural gas and the co-produced flowback water from the XJC 1 well in Junggar Basin, China, were analyzed to determine the origin of gases in the Permian Lucaogou Formation (P2l) and the Triassic Karamay Formation (T2k) in the Bogda Mountain periphery area of the Southern Junggar Basin. The value of carbon isotope composition of the P2l lacustrine shale gas in the Junggar Basin was between the shale gas in Chang 7 Formation of Triassic (T1y7) in Ordos Basin and that in Xu 5 Formation of Triassic (T3x5) in Sichuan Basin, and the difference of gas carbon isotope is primarily because their parent materials were different. The comparison between compositions in the flowback water reveals that the P2l water is of NaHCO3 type while the T2k water is of NaCl type, and salinity of the latter is higher than the former, indicating a connection between P2l source rock and the T2k reservoir. In combination with the structural setting in the study area, the gas filling mode was proposed as follows: the gas generated from the lacustrine source rocks of the Permian Lucaogou Formation is stored in nearby lithological reservoirs from the Permian. Petroleum was also transported along the faults to the shallow layer of Karamay Formation over long distances before it entered the Triassic reservoir.